Implementasi Konsep Lean Manufacturing Untuk Meminimalkan Waktu Keterlambatan Penyelesaian Produk â€Aâ€ Sebagai Value Pelanggan (Studi Kasus Pt. Tsw (Tuban Steel Work) - Nuruddin, Abdul Wahid; Surachman, Surachman; Setyanto, Nasir Widha; Soenoko, Rudy (Jurnal Rekayasa Mesin, 2013)
PT. TSW (Tuban Steel Work) is a company engaged in manufacturing fabricated (make to order) with the commitment and the goal of providing effective services, convenient and timely delivery. But in fact, the company's commitment to the purpose can not be achieved that delays the project completion time is not in accordance with the order due date. Based on the observations made in the study, this is due to some events that can not add value or called by the waste (non-value added). This study aims to identify waste, analysis of contributing factors and recommendations for improvement as the system improvement efforts in creating customer value. By using the concept of lean manufacturing this study begins by describing the current state map and weighting of the waste system, waste weights were analyzed by matrix VALSAT used to identify waste in the system, to analyze the causes of waste by fishbone diagram to illustrate the root cause of waste and failures mode system analysis using failure mode and effect analysis (FMEA) to determine the value of risk priority number (RPN) of the potential causes and potential effects of waste that occurs. The results showed that the waste that occurs is that there are waiting on purchasing activities (supplier), marking-up cutting and fit-up welding. From the discussion, the company recommended improving information systems internal-external (supplier) as well as improvements in the fabrication process activities.Key words: lean manufacturing, VSM, VALSAT, RCA, fishbone diagram, FMEA, SCRM, VMI.